DEVELOPMENT OF RENEWABLE ENERGY SOURCES AND ITS IMPACT ON THE ELECTRICITY MARKET AND GRID INFRASTRUCTURE - N.A, Murzakulov; Gulzar, Tajibaeva; Tsyuyxuey, Sya; Nursultan, Iskenderov (Research Focus International Scientific Journal, 2026)
This article examines possible future energy scenarios for the period up to 2030 in the short, medium and long term, and provides detailed information on the current state of the renewable energy sector.